Triggers and Enablers of Disruptive Behavior in Operating Room Staff: A District-Level Investigation - Aroosh, Sajal; Javed, Hasnain; Khan, Imad Ud Din (Indus Journal of Bioscience Research, 2025)
Background: Disruptive behavior in operating theatres (OTs) poses critical risks to patient safety and team efficacy, exacerbated by hierarchical dynamics, resource constraints, and high-pressure workflows. This study investigates triggers and enablers of such behavior among OT staff in district-level tertiary care settings. Methodology: A descriptive cross-sectional study was conducted across three hospitals in District Vehari, Pakistan. Using simple random sampling, 165 OT staff (surgeons, nurses, technologists) with ≥1 year of experience completed a structured questionnaire. Data were analyzed via SPSS (v29), with frequencies and percentages calculated for categorical variables. Results: Verbal abuse (18.8%) and refusal to cooperate (15.8%) were the most frequent disruptive behaviors, while 46.1% of incidents involved overlapping behaviors (e.g., verbal abuse + physical aggression). Key triggers included high workload (14.5% reported often/always), insufficient resources (15.7%), surgeon temperament (11.5%), and scheduling issues (11.5%). Systemic inefficiencies like unclear policies (9.1%) and inadequate ancillary support (13.3%) further aggravated tensions. Hierarchical conflicts and interpersonal friction were prominent, with poor teamwork (9.7%) and personality clashes (11.5%) frequently cited. Conclusion: Disruptive behavior in Operation Theatres stems from multifactorial triggers, including organizational deficits, power asymmetries, and individual stressors. Mitigation requires protocol standardization, resource optimization, and interdisciplinary training to enhance communication and resilience. Addressing hierarchical imbalances and equipment reliability is critical for fostering safer, collaborative OT environments.